Digitalisasi Edukasi Gout Arthritis: Pengembangan Dan Implementasi E-Modul Berbasis Komunitas - Dwi Novitasari; Adita Silvia Fitriana; Dini Yunita Sari (Yayasan Inspirasi El Burhani, 2026)
Introduction: Public health literacy regarding the prevention and control of gout arthritis remains limited, while existing educational media are largely non-digital and do not adequately support independent learning. Community-based interactive e-modules are therefore considered an innovative approach to improving health literacy and promoting preventive behavioral change. Objective: This Community Service Program aimed to provide training and mentoring to the community in utilizing e-modules as tools for independent health education. Method: The program employed an educational–participatory approach involving members of the Hypertension Care Group. The implementation stages included program socialization, development of interactive e-modules, training on e-module utilization, measurement of participants’ uric acid levels, ongoing mentoring through a WhatsApp group, and evaluation of participant behaviors. Result: The results showed that participants had a mean age of 60.42 years, an average body weight of 60.96 kg, and mean blood pressure of 139.47/89.44 mmHg. Female participants predominated (98 participants; 73.3%). Among participants with normal uric acid levels, most exercised regularly more than three times per week, had never undergone routine health check-ups, did not consume uric acid–lowering medication, and did not avoid high-purine foods. A similar pattern was observed among participants with elevated uric acid levels. The mean uric acid levels were 7.77 mg/dL in male participants and 6.66 mg/dL in female participants. Conclusion: The achieved outputs included community-based interactive educational e-modules, improved public health literacy and the submission of Intellectual Property Rights (IPR) for the developed e-modules.